Point-of-care testing and the predictive value of serum myoglobin as a prognostic marker for acute kidney injury requiring dialysis in rhabdomyolysis caused by sjambok and/or community assault blunt injuries - Cheung, Cynthia Tsz Ying (My University, 2022)
Background: Rhabdomyolysis and crush syndrome were initially described where patients were trapped under buildings and rubble for an extended period following disasters such as earthquakes and bombings. Clinical management has been guided from data based on these patients’ injuries and many predictors have been proposed to predict prognosis, but there is no gold standard. In South Africa, crush injuries arising from community assault (CA) and sjambok injuries have a different profile to those from disaster crush injuries. This study determined the prognostic value of different predictive markers including serum myoglobin for the development of Acute Kidney Injury (AKI) due to rhabdomyolysis caused by sjambok and/or CA blunt injuries. Methods: Prospective observational study of all sjambok and/or CA injury patients admitted for inpatient management at Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto – Gauteng, South Africa over 6 months from May to November 2018. Results: The mean patient age was 29 years and 95% were male. The total length of hospital stay ranged 1-27 days (mean 5.1), with median length of stay of 1 day longer in the group with elevated creatinine. Creatinine on admission and the worst creatinine correlated with pH, bicarbonate, lactate, and myoglobin (p<0.001); with the best measure being myoglobin (r=+0.61 on admission and r+0.41 with worst creatinine, p<0.001). Conclusions: Our study suggested that venous bicarbonate and serum myoglobin should be used as predictors of AKI and risk of Acute Renal Failure (ARF) in crush injuries due to community assault and sjambok injuries. A larger-scale study would be necessary to validate these markers and to guide clinical practice.
A research report submitted in fulfilment of the requirements for the degree of Masters Medicine (Surgery) to the Faculty of Health Science, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2022